MORPHOLOGICAL VARIATION OF TUBER AND CLASSIFICATION OF YOGYAKARTA WATER YAM {Dioscorea alata L.) GERMPLASM - Purnomo, Purnomo; Susandarini, Ratna (2010)
Water Yam {Dioscorea alata L.) was species which have morphological variation of vegetative organ especially on stems, leafs, and tubers. Morphological variation of stem and leaf was already observed, and the result show that water yam cultivated variety (cultivar) could be classified base on it's characters, especially based on leaf shape and stem, wing stem, and leaf color (Araki et ah, 1983; Purnomo et al* 2008). Water Yam cultivars have variation on tuber shape and color, but it has hesitate to created the identification key. The objective of the research was to determined the tuber morphological characters, which can be used as a marker to classified cultivars of Water Yam. Samples of tuber were collected from some places in Yogyakarta region, and it's was planted in the collection garden. Morphological characters of tuber were observed i.e. shape, size, skin color, tuber color, fibrous root, and fiber (Schiwaki et al, 2000; Hasan et al., 2006). Data were analyzed descriptively and comparative table of each cultivar (cv.) to created the parallel identification key concerned to Wrater Yam cultivars. The research result showed that Water Yam tuber have four basic shape, cylindrical ( cv. Ulo, Jingking, and Luyung), ovals (cv. Beras and Beras leg}), and obovate (cv. Ungu, Bangkulit, Kuning, and Kendil). Cultivar Ulo has the largest tuber size compared with the other Water Yam cultivars. There were three tuber basic colors i.e. white (cv. Beras. Legi, Ulo, Jingking, and Kendil), violet (cv. Ungu, dan Luyung senggani), white with violet edge (cv. Bangkulit), and yellowish white (cv. Kuning). Hasan et al. (2006) to used tuber color characters to classified the Malaysian water yam cultivars rather than tuber shape. Based on character analyzed discussion, the identification key was arranged consecutively from tuber shape, color, skin color, and taste go in the direction of Yogyakarta water yam cultivars. Key word: Tuber morphology, water yam (D. alata L.), Yogyakarta.